Are T cells the only HIV-1 reservoir?. Issue 1 (December 2016) - Kandathil, Abraham; Sugawara, Sho; Balagopal, Ashwin
Abstract Current antiretroviral therapies have improved the duration and quality of life of people living with HIV-1. However, viral reservoirs impede complete eradication of the virus. Although there are many strategies to eliminate infectious virus, the most actively pursued are latency reversing agents in conjunction with immune modulation. This strategy, known as "shock and kill", has been tested primarily against the most widely recognized HIV-1 latent reservoir found in resting memory CD4+ T cells. This is in part because of the dearth of conclusive evidence about the existence of non-T cell reservoirs. Studies of non-T cell reservoirs have been difficult to interpret because of technical and biological issues that have hampered a better understanding. This review considers the current knowledge of non-T cell reservoirs, the challenges encountered in a better understanding of these populations, and their implications for HIV-1 cure research.